Making the Bible French: the Bible historiale and the medieval lay reader - Patterson, Jeanette (University of Toronto Press, 2022)
Making the French Bible, or Making the Bible French -- Telling It Right: Confronting Reader Resistance -- Soothing Listeners' Ears: Narrative Aesthetics and Poetic Faith -- Les paroles dont je vous ay fait mention: The Bible historiale's Two Books of Job -- The Patient Reader.